(untitled) (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2019)
Indonesian Republic Law No.45 of 2009 concerning fisheries states that fishing ports have government and business function to support activities related to marketing distribution. In the activities of catch distribution, fishing ports are seen as one part of a single supply chain system. This study was aimed to determine the potential of primary caught fish that landed at PPN Kejawanan and review of supply chain performance in catch distribution activities. The research methods are survey method and in-depth interview with respondents who related to the supply chain. Data analysis was performed by analysis of Location Quotient (LQ) and descriptive analysis. The results showed that primary fish commodities had a 3 score positive growth values of LQ, which were Squid, Stringray, flying fish, and Tetengkek fish, respectively. The 3 score of LQ indicates those fish are relatively concentrated landed in PPN Kejawanan and can continue to be developed. The supply chain performance assessment showed that there was 80% of the criteria already in the supply chain. while 20% of the criteria did not yet exist. In general condition, the supply chain of fish caught by primary commodities, especially squid, is appropriate but still not optimal.